From Drive-Thru to Trust: The Impact of CSR and Social Media Advertising on Customer Retention in the QSR Sector - Kun Peng Xia; Yong Yu Lee; Ann Xuan Khoo; Joanne Xing Yi Lim; Joey Wan Teng Low; Joey Rui Yu Then; Keerthana A/P Kalyselvan; Darshini J; A. J. Ali; Daisy Mui Hung Kee (AIBPM Publisher, 2025)
As corporate social responsibility (CSR) and digital engagement become increasingly influential in shaping consumer behavior, brands must align with customer values while fostering meaningful connections. This study investigates how McDonald’s perceived CSR climate and social media advertising effectiveness impact customer retention, with brand value alignment and customer–organization relationships as mediating variables. Data were collected from 121 McDonald’s customers in Malaysia and analyzed using path analysis in R. The results indicate that CSR climate (? = -0.234, p 0.05) and social media advertising effectiveness (? = -0.050, p 0.05) do not directly influence retention. Instead, both factors positively affect brand value alignment (? = 0.536 and ? = 0.419, respectively; p 0.001), which subsequently enhances customer–organization relationships (? = 0.219, p 0.01) and, in turn, strongly drives customer retention (? = 0.828, p 0.001). The model explains 59% to 67% of the variance in key outcomes (R² = 0.590–0.672). This study offers a unified framework linking CSR and digital marketing to retention outcomes and provides practical insights for fast-food brands aiming to build loyalty through value-based and relational strategies in emerging markets.